2014
DOI: 10.1016/j.jmb.2013.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Scan of Core Positions in Ubiquitin Reveals Links between Dynamics, Stability, and Function

Abstract: Mutations at solvent inaccessible core positions in proteins can impact function through many biophysical mechanisms including alterations to thermodynamic stability and protein dynamics. As these properties of proteins are difficult to investigate, the impacts of core mutations on protein function are poorly understood for most systems. Here, we determined the effects of alanine mutations at all 15 core positions in ubiquitin on function in yeast. The majority (13 of 15) of alanine substitutions supported yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Of the 16 core positions, 13 have aliphatic side chains in wild-type ubiquitin (six Leu, four Ile, and three Val) that form a hydrophobic cluster known to be a driving force for stabilizing native protein structures 42; 43 . Consistent with observations that the protein folding stability of wild-type ubiquitin is far greater than required for yeast growth 27; 44 , we observed that modest substitutions to other aliphatic side chains were generally well tolerated for activation by E1 (Supplementary Fig. S3b).…”
Section: Resultssupporting
confidence: 88%
“…Of the 16 core positions, 13 have aliphatic side chains in wild-type ubiquitin (six Leu, four Ile, and three Val) that form a hydrophobic cluster known to be a driving force for stabilizing native protein structures 42; 43 . Consistent with observations that the protein folding stability of wild-type ubiquitin is far greater than required for yeast growth 27; 44 , we observed that modest substitutions to other aliphatic side chains were generally well tolerated for activation by E1 (Supplementary Fig. S3b).…”
Section: Resultssupporting
confidence: 88%
“…While these caveats are a concern, the SUB328 experimental system has been successfully used for many years to assess the effect of Ub mutations in yeast (Roscoe et al, 2013;SloperMould et al, 2001;Lee et al, 2014). Furthermore, we have only interpreted mutants that cause large defects, such as the biologically sensible fitness defects of mutations at known important residues such as Leu8 or Lys48 and residues with fitness values that vary between conditions such as His68.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most fundamental observations of protein conformational dynamics and their contributions to function come from NMR analyses of enzymes where highly specific protein motions can be required for efficient catalysis (Eisenmesser et al 2002;Villali and Kern 2010). Recent systematic analyses of mutations in proteins or regions of proteins involved in protein-protein interactions (Jiang et al 2013;Lee et al 2014; indicate that binding functions can also be very sensitive to protein conformational changes less severe than complete unfolding. This inference comes largely from observations that many amino acid substitutions at solvent inaccessible positions in these binding proteins cause strong functional defects without causing protein unfolding.…”
Section: Structural Interpretations Of Local Mutational Landscapesmentioning
confidence: 99%
“…In addition, ubiquitin primarily acts through protein-protein binding interactions. Despite these features, many mutations in the core of ubiquitin that cause subtle alterations to the conformational properties of ubiquitin have large impacts on its binding functions (Phillips et al 2013;Lee et al 2014;. Further studies on additional proteins should provide valuable insights into the generality of these observations for binding proteins and the nature of biophysical constraints in these systems.…”
Section: Structural Interpretations Of Local Mutational Landscapesmentioning
confidence: 99%